Real-Time AI Decision Making in IoT with Quantum Computing: Investigating & Exploring the Development and Implementation of Quantum-Supported AI Inference Systems for IoT Applications (Internet of Things and Edge Computing Journal, 2021)
The Internet of Things (IoT) has revolutionized the way devices communicate and interact, generating vast amounts of data that require real-time processing and decision-making capabilities. Traditional AI systems face challenges in meeting the real-time demands of IoT applications due to computational complexities. Quantum computing has emerged as a potential solution, offering parallel processing power to accelerate AI inference tasks. This paper investigates the integration of quantum computing into AI systems for real-time decision-making in IoT. We explore the development, challenges, and future prospects of quantum-supported AI inference systems for IoT applications, highlighting the potential benefits and limitations of this approach. Through a comprehensive review of existing literature and case studies, we provide insights into the current state of quantum-supported AI inference systems in IoT and discuss the implications for future research and development in this field.